2006
DOI: 10.1136/ip.2005.010942
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of bicycle helmet legislation to increase helmet use: a systematic review

Abstract: Background: Head injuries related to bicycle use are common and can be serious. They can be prevented or reduced in severity with helmet use; however, education has resulted in modest helmet use in most developed countries. Helmet legislation has been proposed as a method to increase helmet wearing; while this social intervention is thought to be effective, no systematic review has been performed. Objectives: This review evaluates the scientific evidence for helmet use following legislation to identify the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(93 citation statements)
references
References 30 publications
7
83
1
2
Order By: Relevance
“…28,37 Legislation has been found to effectively increase helmet use and decrease head injury rates. 38,39 After introduction of helmet laws in Victoria, Australia, helmet use increased from 31% to 75%, and cycling fatalities decreased by 48%. 36,40 A 2010 Canadian study found that youth and adults were significantly more likely to wear helmets as the comprehensiveness of helmet legislation increased, and that helmet legislation was not associated with changes in ridership.…”
Section: Legislationmentioning
confidence: 99%
“…28,37 Legislation has been found to effectively increase helmet use and decrease head injury rates. 38,39 After introduction of helmet laws in Victoria, Australia, helmet use increased from 31% to 75%, and cycling fatalities decreased by 48%. 36,40 A 2010 Canadian study found that youth and adults were significantly more likely to wear helmets as the comprehensiveness of helmet legislation increased, and that helmet legislation was not associated with changes in ridership.…”
Section: Legislationmentioning
confidence: 99%
“…Existe un debate sobre si legislar el uso obligatorio del casco, como han sugerido algunos autores [18][19][20] . Se considera una medida efectiva para incrementar su uso y disminuir el número de lesiones y de muertes en ciclistas 21 .…”
Section: Discussionunclassified
“…Effectiveness: Two systematic reviews, of 12 studies and three studies respectively, using different study inclusion criteria found that legislation may be effective at increasing helmet use (Karkhaneh, Kalenga, Hagel, & Rowe, 2006;Macpherson & Spinks, 2007). The degree of improvement varied but there was a lack of evidence to determine whether enforcement, supporting publicity, and helmet distribution efforts explain some of the variation (Karkhaneh et al, 2006;Macpherson & Spinks, 2007).…”
Section: Childrenmentioning
confidence: 99%